The Role of Bakau Snail, Telescopium telescopium L., as Biofilter in Waste Water Management of Intensive Shrimp Culture - Hamsiah; Djokosetiyanto, Daniel; Adiwilaga, E. M.; Nirmala, Kukuh (Indonesian Society of Scientific Aquaculture (ISSA), 2002)
ABSTRACTThe objective the experiment is to know the role of bakau snail, Telescopium telescopium L., as biofilter for improving waste water quality in shrimp culture. The experiment was carried out at laboratory scale. The parameters that observed in this experiment are physical, chemical and biological of waste water. Growth and survival rate of snail were also observed. Waste water quality measurement was carried out during a week, while the growth and survival rate were measured during two months. The aquarium of 30x40x40 cm were filled with 30 l of waste water from intensive shrimp culture. Bakau snail were stocked to the aquarium with density of 0 (control), 6, 9 and 12 snail/aquarium, and these treatment were replicated 3 times. The result shown that total organic matter (TOM), total ammonia, dissolved oxygen (DO) of waste water, and growth and survival rate of snail were not different between treatment of stocking density, while the biological oxygen demand (BOD), total suspended solid (TSS), nitrite and nitrate were significantly different (pKey words : Bakau snail, Telescopium telescopium L., biofilter, shrimp culture waste water. ABSTRAKPercobaan ini bertujuan untuk mengkaji peranan keong bakau, Telescopium telescopium L., sebagai biofilter terhadap perbaikan mutu air limbah budidaya tambak udang intesif. Pertumbuhan dan kelangsungan hidup keong bakau juga dikaji. Percobaan dilakukan dalam skala laboratorium. Pengamatan kualitas air fisika, kimia dan biologi air limbah budidaya tambak dilakukan selama seminggu, sedangkan pertumbuhan keong dilakukan selama 2 bulan. Wadah percobaan yang digunakan adalah akuarium ukuran 30x40x40 cm dan diisi air sebanyak 30 liter yang berasal dari buangan budidaya udang intensif di tambak. Perlakuan percoban berupa padat tebar keong bakau dalam akuarium yaitu: 0 (tanpa keong), 6, 9 dan 13 ekor/akuarium, dan setiap perlakuan diulang 3 kali. Hasil percobaan menunjukkan bahwa respon peubah kadar bahan organik total (TOM), amoniak total, oksigen terlarut (DO) dalam air limbah, serta pertumbuhan dan kelangsungan hidup keong bakau tidak berbeda antar perlakuan kepadatan, sedangkan BOD5, padatan tersuspensi total (TSS), nitrit dan nitrat berbeda nyata (pKata kunci : Keong bakau, Telescopium telescopium L., biofilter, air limbah budidaya udang.